Challenges and Solutions to the Commercialization of Professional Leagues: A Case Study of Rugby - Sun, Kaige (Transactions on Economics, Business and Management Research, 2024)
The commercialization of professional leagues has become an important trend in the global sports industry, and rugby faces unique challenges in this process. Although rugby has a profound cultural foundation and social influence in the Commonwealth countries, compared with global sports such as football and basketball, its commercialization process still lags behind. The ever-rising expectations of spectators for sporting events make it necessary for the league to strike a balance between maintaining its traditional culture and adapting to the demands of modern business. In addition, the global sports market is highly competitive, and rugby leagues need to effectively attract viewers and sponsors, while coping with the changing consumer habits of the digital age. The aim of this study is to explore the main challenges and strategies in the commercialization process of rugby professional league, so as to enhance its market competitiveness and brand impact. Most of the studies on the commercialization of professional leagues focus on football and basketball, but few on rugby, which mainly includes economic benefits, marketing strategies and organizational management.